Proses Berpikir Siswa Level Visualisasi dalam Menyelesaikan Masalah Dimensi Tiga berdasarkan Langkah-Langkah Polya - Ariel Bachtiar Ramadhani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this research is to describe the thinking process of visualization level students in solving three-dimensional problems based on Polya's steps. This type of research is descriptive research with a qualitative approach. This research was conducted at SMK Ar-Raudlah. The subjects of this research consisted of 2 visualization level students. This research uses test and interview methods. The instruments used in this study include the VHGT test, problem solving test and interview guidelines. The results of the VHGT test in this study, only found pre-visualization, visualization and analysis levels with percentages of 58.33%, 29.17% and 4.17% respectively. Furthermore, visualization level students were given a problem solving test to find out the students' thinking process in solving three-dimensional problems. The results of this study showed that the thinking process of visualization level students in solving three-dimensional problems into four steps, namely understanding the problem, devising a plan, carrying out the plan, and looking back. When understanding the three-dimensional problem, equilibrium events occur when students are able to identify the conditions in the problem and are able to sketch the image of the problem. When devising a plan, equilibrium events occur when students are able to determine the plan to be used by using all the information that has been obtained to solve the problem through drawings. At the time of carrying out the plan, equilibrium events occur when students are able to ensure and solve problems according to the plan. When looking back, equilibrium events occur when students are able to re-explain the results of solving the problem.
Entry oleh Arif 2026 Maret 16
Keywords: Geometry; the Polya Problem-Solving Method; Van Hiele